Tracheal and Cricotracheal Resection With End-to-End Anastomosis for Locally Advanced Thyroid Cancer: A Systematic Review of the Literature on 656 Patients - Piazza, Cesare; Lancini, Davide; Tomasoni, Michele; D’Cruz, Anil; Hartl, Dana M.; Kowalski, Luiz P.; Randolph, Gregory W.; Rinaldo, Alessandra; Shah, Jatin P.; Shaha, Ashok R.; Simo, Ricard; Vander Poorten, Vincent; et al. (Frontiers in Endocrinology, 2021)
Airway involvement by advanced thyroid carcinoma (TC) constitutes a negative prognosticator, besides being a critical clinical issue since it represents one of the most frequent causes of death in locally advanced disease. It is generally agreed that, for appropriate laryngo-tracheal patterns of invasion, (crico-)tracheal resection and primary anastomosis [(C)TRA] is the preferred surgical technique in this clinical scenario. However, the results of long-term outcomes of (C)TRA are scarce in the literature, due to the rarity of such cases. The relative paucity of data prompts careful review of the available relevant series in order to critically evaluate this surgical technique from the oncologic and functional points of view. A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement on the PubMed, Scopus, and Web of Science databases. English-language surgical series published between January 1985 and August 2021, reporting data on ≥5 patients treated for TC infiltrating the airway by (C)TRA were included. Oncologic outcomes, mortality, complications, and tracheotomy-dependency rates were assessed. Pooled proportion estimates were elaborated for each end-point. Thirty-seven studies were included, encompassing a total of 656 patients. Pooled risk of perioperative mortality was 2.0%. Surgical complications were reported in 27.0% of patients, with uni- or bilateral recurrent laryngeal nerve palsy being the most common. Permanent tracheotomy was required in 4.0% of patients. Oncologic outcomes varied among different series with 5- and 10-year overall survival rates ranging from 61% to 100% and 42.1% to 78.1%, respectively. Five- and 10-year disease specific survival rates ranged from 75.8% to 90% and 54.5% to 62.9%, respectively. Therefore, locally advanced TC with airway invasion treated with (C)TRA provides acceptable oncologic outcomes associated with a low permanent tracheotomy rate. The reported incidence of complications, however, indicates the need for judicious patient selection, meticulous surgical technique, and careful postoperative management.